Dampak Sistem Pengendalian Internal terhadap Kualitas Laporan Keuangan dan Pemanfaatan Teknologi Informasi sebagai Pemoderasi - Ryandika Ramadhan Al Farishi; Lauw Tjun Tjun (Journal of Accounting, Finance, Taxation, and Auditing (JAFTA), 2023)
The purpose of this research is to evaluate the impact of Internal Control System (SPI) on the quality of financial reports (KLK) with the use of Information Technology (PTI) as a moderator. The research method adopted is quantitative. The data utilized in this study are primary data collected through an online questionnaire distributed via Google Forms. The data analysis technique employed is Partial Least Square (PLS) using smartPLS 3 software, with a total of 45 respondents from manufacturing companies in West Java. The research findings indicate that SPI has a significant positive impact, and PTI strengthens the influence of SPI on KLK. Limitations of the study include difficulties in collecting online questionnaire data according to the required criteria. The contribution of this research lies in the fact that PTI can enhance the implementation of SPI on KLK.